2018
DOI: 10.1016/j.jadohealth.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccine-Related Risk Perceptions Do Not Predict Sexual Initiation Among Young Women Over 30 Months Following Vaccination

Abstract: HPV vaccine-related risk perceptions were not associated with sexual initiation or age of sexual initiation, providing further support that HPV vaccine-related risk perceptions are unlikely to lead to riskier sexual behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
3
2
0
Order By: Relevance
“…Furthermore, other countries have reported declines in sexual activity among adolescents since HPV vaccine introduction [20]. These findings complement other studies, which report no association between vaccination and sexual initiation [21], other sexually transmitted infections or teen pregnancy [22], or other sexual risk behaviors [23]. Although reasons for downward trends in adolescent sexual behavior are unknown and likely multifactorial, no data suggest that HPV vaccination increases adolescent sexual risk behavior.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, other countries have reported declines in sexual activity among adolescents since HPV vaccine introduction [20]. These findings complement other studies, which report no association between vaccination and sexual initiation [21], other sexually transmitted infections or teen pregnancy [22], or other sexual risk behaviors [23]. Although reasons for downward trends in adolescent sexual behavior are unknown and likely multifactorial, no data suggest that HPV vaccination increases adolescent sexual risk behavior.…”
Section: Discussionsupporting
confidence: 74%
“…Our LSA findings demonstrated that, on Reddit, cancer is significantly more discussed than sexual activity, consistent with the majority of prior research [14,38,39]. Although HPV cancer risk prevention and HPV-related sexuality are presented as competing narratives in the broader media discourse, these two topics alone do not reflect the focus of the majority of HPV-related conversations on Reddit.…”
Section: Discussionsupporting
confidence: 85%
“…Our LSA findings demonstrated that, on Reddit, cancer is significantly more discussed than sexual activity, consistent with the majority of prior research [14,38,39]…”
Section: Principal Findingssupporting
confidence: 90%